(untitled) (Research, Society and Development, 2021)
The quality of life of pregnant women who choose normal childbirth leads to public and local health considerations. A normal birth leads to changes in the pelvic floor muscles that can lead to physiological complications. Presenting information about physical therapy conduct in the preparation of pelvic strengthening after vaginal delivery are the main objectives of this work. The study was presented as a literature review through scientific articles published in national and international scientific journals. Papers indexed in the databases ScienceDirecct, PubMed, Medline, Web of Science, EMBASE, LILACS, Scielo and Academic Google were selected. Human anatomy of the pelvic floor, its innervations and contexts were presented in this work, indexed works that involve the contextualization of normal birth, pelvic floor, diseases and their aspects were also contemplated. A physical therapy program in these situations is extremely important for the quality of life of women and associates.